دور دراسة الجدوى التسويقية في نجاح المشروعات الإقتصادية - جار الله صليحة; بن جاب الله محمد (جامعة عمار ثليجي الاغواط, 2021)
This study aims to shed light on the subject of the economic feasibility study in general and marketing feasibility in particular as one of the important mechanisms in the success of economic projects, so that this study contains a series of accurate and detailed studies aimed at achieving the image of the economic project on the ground before its launch, and the success of the feasibility study is based The economic project, including the success of the economic project, relies on two basic elements, namely, the availability of information and data that are considered among the economic feasibility studies, as well as the one who prepares them in itself must be qualified and an expert in the field of projects and the preparation of feasibility studies. The detailed study also contributes to drawing a comprehensive picture that includes all aspects and marketing factors. The environmental, technical aspects of the economic project, including the need to pay attention to economic feasibility studies because of their importance in the success of economic projects, especially marketing feasibility, as well as intensifying training and training courses in preparing economic feasibility studies.